The effects of using phonics reading software on primary level ESL learners' reading skills - Baiti, Nabilla Shariff Abdulla (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study explores the use of phonics software in language reading skills. The study observes the effects of using phonics software to improve young English language learners' reading abilities. The study employs a quasi-experimental design. It consists of an experimental group which has received learning through the phonics software as a part of its reading lessons. The other group is the control group which has received learning without the software. The control group has acquired the reading skill through conventional classroom tools. A set of pre-tests and posttests are used as the instrument to collect data for the research. The findings indicate that both groups showed marked improvement. This suggests that the availability of both methods is fundamental in teaching of reading. However, the experimental group performed slightly better than the control group. This indicates that schools should use the phonics software to teach reading skills as it is able to stimulate learners to not only learn the basics faster but also in a more interactive manner. This does not mean that the conventional classroom tools are unsuitable to teach reading. Hence, the study indicates that both methods should be integrated to create a more holistic approach to learn reading skills.